Effect of package lining on quality and shelf-life of papaya fruits - E. Shattir, Adil; A. Abu-Goukh, Abu-Bakr (Gezira Journal of Agricultural Science; Vol 10 No 2 (2012), 2023)
The effect of package lining on quality and shelf-life of ‘Baladi’ and ‘Ekostika II’ papaya fruits at 18 ± 1 o C and 85% – 90% relative humidity was evaluated. Package lining with paper or polyethylene sheets significantly delayed fruit ripening by one and three days, respectively, compared to unlined fruits (control) in both cultivars. Polyethylene film liners were more effective in extending the shelf-life of fruits than paper liners, due to more restriction to gas exchange than with paper liners. The effect of package lining in delaying papaya fruit ripening was reflected in reduced respiration rate, delayed the onset of climacteric peak, decreased water loss, delayed fruit softening, accumulation of TSS, total and reducing sugars and ascorbic acid content in fruits.